2016
DOI: 10.1002/ppul.23545
|View full text |Cite
|
Sign up to set email alerts
|

Estimating pediatric asthma prevalence in rural senegal: A cross‐sectional survey

Abstract: Nearly one in ten children in Niakhar, Senegal had symptoms suggestive of asthma; however, few children have a diagnosis of asthma or use appropriate therapies. This study highlights an opportunity to raise community awareness of asthma in rural Senegal and to increase access to appropriate medical therapies. Pediatr Pulmonol. 2017;52:303-309. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…A possible limitation in this study was also the subjective measure of indoor exposures of potential allergens and chemical pollutants from cooking fuels, which was not corroborated with objective environmental measurements. However, our findings are similar to other studies that have used similar subjective assessments of indoor pollutants …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A possible limitation in this study was also the subjective measure of indoor exposures of potential allergens and chemical pollutants from cooking fuels, which was not corroborated with objective environmental measurements. However, our findings are similar to other studies that have used similar subjective assessments of indoor pollutants …”
Section: Discussionsupporting
confidence: 92%
“…However, the prevalence of doctor‐diagnosed asthma reported in this study is within the range of those reported in the global pediatric asthma prevalence surveys on African children with reported proportions from 2.5% in Ethiopia and Burkina Faso to almost 10% in Swaziland . The prevalence of doctor‐diagnosed asthma from recent cross‐sectional studies from other low‐ and middle‐income countries were as high as 7.5% in Iran, 6% in India, 4.8% in China, 3% in Senegal, 2.5% in Mongolia, to 2% in Georgia …”
Section: Discussionsupporting
confidence: 71%
“…In a cross‐sectional study conducted in rural Senegal (west Africa) from a total of 1513 children aged 6‐7 years, 130 (9%) reported wheezing within the last 12 months, and 41 (3%) had a clinical asthma diagnosis which were compatible with the results of the current study. Our results showed that the prevalence of wheezing within the last year was higher in 6‐ to 7‐year olds (7.8%) while lower prevalence was obtained in participants aged 13‐14 years (9.5%).…”
Section: Discussionsupporting
confidence: 88%
“…However, depending on exposure to these stoves, opinions may have been based on a specific stove design rather than the broader category of ICS. Finally, in the context of a preceding survey asking questions about child respiratory symptoms related to smoke [ 21 ], participants may have been inclined to report dissatisfaction with their traditional open-fire stove and show enhanced interest in alternative technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The largest villages were more consistently accessible during the rainy seasons and including them allowed our field workers to contact the greatest number of households within a defined geographic area. This survey was co-administered with a survey on asthma symptoms in children [ 21 ]. All households within each village with at least one child aged five through eight years old (the inclusion criteria for the asthma portion) were included.…”
Section: Methodsmentioning
confidence: 99%